Engineering Manager: Constitutive Elements of this Profession. Issue 1 (2nd January 2019) - Fischer, Jelena; Pecujlija, Mladen; Cosic, Djordje; Lalic, Bojan
ABSTRACT: With a sample of 358 students of engineering management and 195 engineering managers, using an ad hoc questionnaire, the paper examines the importance of professional ethics as a constitutive element of the engineering management profession in Serbia. The results indicate that professional ethics is an essential element of constituting this relatively young profession in Serbia.